Gene Mining and Germplasm Innovation for the Important Traits in Rice (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
Rice is one of the major crops and feeds half of the population worldwide. Diseases caused by fungi, bacteria, or viruses seriously affect rice yield and quality. Breeding new resistant rice varieties is the simplest and most effective management for diseases.In recent years, rice has been recognized as a genetic model for molecular biology research aimed toward understanding mechanisms of disease resistance. Up until now, great progress has been made in the molecular genetics of rice disease resistance. Over 150 QTLs associated with rice disease resistance have been identified and more than 50 resistance genes have been cloned. This Special Issue of IJMS aims to highlight the following areas: Screening and improvement of rice-disease-resistant germplasms; Breeding of disease-resistant rice cultivars; Methods of inoculation and rating investigation; Mapping and cloning of resistance genes; Molecular genetics analysis of resistance (such as GWASs); Molecular biology research on resistance; Mechanisms of rice–pathogen interaction.